Technology-based approach for managing large classes : A case study - Narayanan, A/L N. Kulathu Ramaiyer; Farid, Meziane (Universiti Malaysia Sarawak (UNIMAS), 1997)
Educational institutions are faced with many problems. In one hand they face a shortage of staff and funding and at the same time the number of students enrolled is ever increasing. The lecturers are faced with large and sometimes huge classes. Providing a quality course using traditional methods of teaching- learning becomes very difficult if not impossible. This calls for a shift in the teaching-learning paradigm whereby the traditional modes become inadequate to both deal with the large number of students and to provide an interactive learning environment. Technologybased and student-centred approaches need to be employed to overcome the space-time barriers in this new environment.